2018
DOI: 10.15614/ijpp.v9i01.11749
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy culture as a moderator on the relationship between work motivation and work commitment

Abstract: For the understanding of economic and cultural advancement in a society, higher education is one of the key factors.Present study intended to examine the role of hierarchy culture as a moderator on the relationship between work motivation and work commitment among university teachers. The study design was based on quantitative methods. Sample comprised of 351 teachers from public universities of Punjab, Pakistan. Multivariate analysis and descriptive statistics were performed using Smart PLS 3.0. Findings conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
2
1
1
Order By: Relevance
“…Commitment can increase or hinder employees' willingness to do work because it affects their productivity and quality of work. This study's findings align with previous findings regarding the impact of commitment on employee performance (Irfan & Marzuki, 2018;Loan, 2020). Employees who demonstrate a more outstanding value-based commitment to their organization are more likely to engage in knowledge sharing, decrease absenteeism and lead to higher performance levels (Beloor et al, 2017;Cesário & Chambel, 2017).…”
Section: Work Commitmentsupporting
confidence: 87%
See 1 more Smart Citation
“…Commitment can increase or hinder employees' willingness to do work because it affects their productivity and quality of work. This study's findings align with previous findings regarding the impact of commitment on employee performance (Irfan & Marzuki, 2018;Loan, 2020). Employees who demonstrate a more outstanding value-based commitment to their organization are more likely to engage in knowledge sharing, decrease absenteeism and lead to higher performance levels (Beloor et al, 2017;Cesário & Chambel, 2017).…”
Section: Work Commitmentsupporting
confidence: 87%
“…Organizational commitment is not related to performance (Zefeiti & Noor Azmi, 2017). Nevertheless, many researchers argue that there is a positive relationship between organizational commitment and performance (Al-Muallem & Al-Surimi, 2019;Irfan & Marzuki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Authors like Uzkurt et al (2013) asserted that organizations with innovative workforce have been found more goal oriented; thereby investigating the role of organizational innovation is important. A significant and direct relationship is found between organizational innovation and achieving organizational goal (Ha & Lo, 2018); Hurley and Choudhary (2016); (Irfan & Marzuki, 2018); Powell (2012); Robson (2013); (Uddin et al, 2013;Uzkurt et al, 2013). Contrary to previous studies, the current study extends the body of knowledge and outlined organizational innovation as moderating variable between achieving strategic goal and organizational productivity (Manu, 1992;Narver, Slater, & MacLachlan, 2004;Noble, Sinha, & Kumar, 2002;Siguaw, Simpson, & Enz, 2006).…”
Section: Organizational Innovationcontrasting
confidence: 54%
“…Although the focus of this study was to investigate employee commitment towards achieving strategic goal of firm and organizational productivity, it added organizational innovation in the research model. Organization innovation is identified as organization efforts to bring and adopt new and unique methods to carry on daily business activities (Ha & Lo, 2018;Hurley & Choudhary, 2016;Irfan & Marzuki, 2018;Jimenez-Jimenez, Sanz Valle, & Hernandez-Espallardo, 2008;Okoye, 2007;Powell, 2012;Robson, 2013;Uddin, Luva, & Hossian, 2013;Uzkurt, Kumar, Semih Kimzan, & Eminoğlu, 2013). Thereby, the role of organizational innovation is studied as moderator between achieving strategic goal of the firm and organisational productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Dari hasil tersebut dapat dimanfaatkan bagi pembuat kebijakan untuk memotivasi bawahan untuk bekerja sehingga budaya kerja dapat dilaksankan secara terstruktur dan terkontrol. Temuan studi juga mengusulkan pengembangan budaya suportif untuk meningkatkan komitmen kerja (Irfan & Marzuki, 2018). Profil dikaitkan dengan hasil kesejahteraan (kenikmatan kerja, daya apung di tempat kerja, pelepasan kerja) dan karakteristik pribadi dan pekerjaan guru (Collie & Martin, 2017).…”
unclassified